Changing epidemiology of chronic hepatitis C: patients are older and at a more advanced stage at the time of diagnosis. Issue 10 (October 2019) - Iliaz, Raim; Yuce, Tuba; Torun, Sinan; Cavus, Bilger; Gulluoglu, Mine; Bozaci, Muruvvet; Karaca, Cetin; Akyuz, Filiz; Demir, Kadir; Besisik, Fatih; Kaymakoglu, Sabahattin
Abstract : Introduction and aim: Over the years, there has been a change in the profile of patients with chronic hepatitis C (CHC). In recent years, more patients with CHC have presented to the clinics at the cirrhotic stage, with decompensated liver disease, and with hepatocellular carcinoma. The aim of this study was to investigate the changing epidemiological, clinical, and virological characteristics of CHC patients. Patients and methods: A total of 313 CHC patients were included in this study. The patients were classified into group 1 (1996–2001) and group 2 (2011–2016). Epidemiological, clinical, and virological differences were investigated between two periods. Results: Overall, 44.7% ( n = 140) of the patients were in group 1. The sex distribution between the two groups was similar. The patients in group 2 was older than those in group 1 (54 ± 15 vs. 45 ± 12 years, retrospectively, P < 0.001). Whereas 19.8% of the patients in group 1 were treatment-experienced, this rate was found to be 35.5% in group 2 ( P = 0.01). Patients who presented in the first period had fewer comorbidities compared with group 2 ( P < 0.001). More patients in group 2 had liver cirrhosis than group 1 (45.1 vs. 18.6%, respectively, P < 0.001). Among the patients with cirrhosis, the rate of decompensation was higher in group 2 (46.7 vs. 23.3%, P = 0.03). The presence of hepatocellular carcinoma was significantly higher in group 2 than group 1 (12.8 vs. 3.6%, respectively, P = 0.004). Conclusion: In recent years, CHC patients have presented to hospitals with advanced stage of liver disease; these patients are older and have more comorbidities.